2014
DOI: 10.1051/0004-6361/201321521
|View full text |Cite
|
Sign up to set email alerts
|

Planck2013 results. XX. Cosmology from Sunyaev–Zeldovich cluster counts

Abstract: We present constraints on cosmological parameters using number counts as a function of redshift for a sub-sample of 189 galaxy clusters from the Planck SZ (PSZ) catalogue. The PSZ is selected through the signature of the Sunyaev-Zeldovich (SZ) effect, and the sub-sample used here has a signal-to-noise threshold of seven, with each object confirmed as a cluster and all but one with a redshift estimate. We discuss the completeness of the sample and our construction of a likelihood analysis. Using a relation betw… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
158
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 512 publications
(165 citation statements)
references
References 127 publications
7
158
0
Order By: Relevance
“…allowed regions in the (σ8, H0) plane for different models: ΛCDM+νs (gray), MOD1+νs (red) and MOD2+νs (blue), obtained with the full data combination considered here ("ALL"). The vertical green band denotes the interval H0 = 70.6 ± 3.3 Km s −1 Mpc −1 [67] (GE), while the horizontal dark yellow band stands for σ8 = 0.75 ± 0.03 [60] (SZ).…”
Section: Discussionmentioning
confidence: 99%
“…allowed regions in the (σ8, H0) plane for different models: ΛCDM+νs (gray), MOD1+νs (red) and MOD2+νs (blue), obtained with the full data combination considered here ("ALL"). The vertical green band denotes the interval H0 = 70.6 ± 3.3 Km s −1 Mpc −1 [67] (GE), while the horizontal dark yellow band stands for σ8 = 0.75 ± 0.03 [60] (SZ).…”
Section: Discussionmentioning
confidence: 99%
“…However, it has been found that several important astrophysical observations are inconsistent with the Planck observation (based on the CDM cosmology), to some extent. For example, the fit results of the six-parameter a e-mail: zhangxin@mail.neu.edu.cn base CDM model based on the Planck+WP+highL data [11] are in tension with the direct measurement of the Hubble constant [12], the Planck Sunyaev-Zeldovich clusters counts [13], and the cosmic shear measurement of CFHTLenS survey [14].…”
Section: Introductionmentioning
confidence: 99%
“…The neutrino-induced suppression to the matter power spectrum scales primarily with i m νi and current bounds on the sum of the neutrino masses from cosmological datasets are i m νi ∼ < 0.2eV − 1eV (see e.g. [1][2][3][4] for CMB constraints, [7][8][9][10][11][12][13][14][15][16] for constraints from galaxy and Lyman-alpha forest surveys, and [17][18][19][20][21][22] for constraints from the abundance of galaxy clusters).…”
Section: Introductionmentioning
confidence: 99%